All Science Fair Projects

Science Fair Project Encyclopedia for Schools!

 Search    Browse    Forum  Coach    Links    Editor    Help    Tell-a-Friend    Encyclopedia    Dictionary

Science Fair Project Encyclopedia

For information on any area of science that interests you,
enter a keyword (eg. scientific method, molecule, cloud, carbohydrate etc.).
Or else, you can start by choosing any of the categories below.

Bridgman's thermodynamic equations

(Redirected from Bridgman's equations)

In Thermodynamics, Bridgman's Thermodynamic equations is actually a method of generating a large number of thermodynamic identities involving a number of thermodynamic quantities. Some of the most common thermodynamic quantites are:

 Internal energy U Helmholtz free energy F Gibbs free energy G Enthalpy H Particle number N Pressure P Density ρ Entropy S Temperature T Specific heat (constant volume) CV Specific heat (constant pressure) CP Volume V

Many thermodynamic equations are expressed in terms of partial derivatives. For example, the expression for the specific heat at constant volume is:

$C_P=\left(\frac{\partial H}{\partial T}\right)_P$

which is the partial derivative of the internal energy with respect to temperature while holding volume constant. We may write this equation as:

$C_P=\frac{(\partial H)_P}{(\partial T)_P}$

This method of rewriting the partial derivative was described by Bridgman (and also Lewis &; Randall), and allows the use of the following collection of expressions to express many thermodynamic equations. For example in the equations below we have:

$(\partial H)_P=C_P$

and

$(\partial T)_P=1$

Dividing, we recover the proper expression for CP.

The following summary restates various partials in terms of S, T, P, and the following three derivatives which are easily measured experimentally.

$\left(\frac{\partial V}{\partial T}\right)_P,~~~ \left(\frac{\partial V}{\partial P}\right)_T,~~~ \left(\frac{\partial H}{\partial T}\right)_P (=C_P)$

Bridgman's thermodynamic equations

$(\partial T)_P=-(\partial P)_T=1$
$(\partial V)_P=-(\partial P)_V=\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial S)_P=-(\partial P)_S=\frac{C_p}{T}$
$(\partial U)_P=-(\partial P)_U=C_P-P\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial H)_P=-(\partial P)_H=C_P$
$(\partial G)_P=-(\partial P)_G=-S$
$(\partial F)_P=-(\partial P)_F=-S-P\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial V)_T=-(\partial T)_V=-\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial S)_T=-(\partial T)_S=\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial U)_T=-(\partial T)_U=T\left(\frac{\partial V}{\partial T}\right)_P+P\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial H)_T=-(\partial T)_H=-V+T\left(\frac{\partial V}{\partial }\right)_P$
$(\partial G)_T=-(\partial T)_G=-V$
$(\partial F)_T=-(\partial T)_F=P\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial S)_V=-(\partial V)_S=\frac{C_P}{T}\left(\frac{\partial V}{\partial P}\right)_T+\left(\frac{\partial V}{\partial T}\right)_P^2$
$(\partial U)_V=-(\partial V)_U=C_P\left(\frac{\partial V}{\partial P}\right)_T+T\left(\frac{\partial V}{\partial T}\right)_P^2$
$(\partial H)_V=-(\partial V)_H=C_P\left(\frac{\partial V}{\partial P}\right)_T+T\left(\frac{\partial V}{\partial T}\right)_P^2-V\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial G)_V=-(\partial V)_G=-V\left(\frac{\partial V}{\partial T}\right)_P-S\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial F)_V=-(\partial V)_F=-S\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial U)_S=-(\partial S)_U=\frac{PC_P}{T}\left(\frac{\partial V}{\partial P}\right)_T+P\left(\frac{\partial V}{\partial T}\right)_P^2$
$(\partial H)_S=-(\partial S)_H=-\frac{VC_P}{T}$
$(\partial G)_S=-(\partial S)_G=-\frac{VC_P}{T}+S\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial F)_S=-(\partial S)_F=\frac{PC_P}{T}\left(\frac{\partial V}{\partial P}\right)_T+P\left(\frac{\partial V}{\partial T}\right)_P^2+S\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial H)_U=-(\partial U)_H=-VC_P+PV\left(\frac{\partial V}{\partial T}\right)_P-PC_P\left(\frac{\partial V}{\partial P}\right)_T-PT\left(\frac{\partial V}{\partial T}\right)_P^2$
$(\partial G)_U=-(\partial U)_G=-VC_P+PV\left(\frac{\partial V}{\partial T}\right)_P+ST\left(\frac{\partial V}{\partial T}\right)_P+SP\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial F)_U=-(\partial U)_F=-P(C_P+S)\left(\frac{\partial V}{\partial P}\right)_T+PT\left(\frac{\partial V}{\partial T}\right)_P^2+ST\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial G)_H=-(\partial H)_G=-V(C_P+S)+TS\left(\frac{\partial V}{\partial T}\right)_P$
$(\partial F)_H=-(\partial H)_F=\left[S+P\left(\frac{\partial V}{\partial T}\right)_P\right]\left[V-T\left(\frac{\partial V}{\partial T}\right)_P\right]+PC_P\left(\frac{\partial V}{\partial P}\right)_T$
$(\partial F)_G=-(\partial G)_F=-SV-_P\left(\frac{\partial V}{\partial P}\right)_T-PV\left(\frac{\partial V}{\partial T}\right)_P$

References

• Bridgman, P.W., Phys. Rev., 3, 273 (1914).
• Lewis, G.N., and Randall, M., "Thermodynamics", 2nd Edition, McGraw-Hill Book Company, New York, 1961.
03-10-2013 05:06:04